Diagnóstico socioambiental para o município de Severiano de Almeida - RS - Burin, Elias (2010)
In the current conjuncture, where the support depends on the balance between environment e development, the present work has as objective to collect, to organize e to analyze social-ambient data and to consider measured of ambient management assisting in the adoption of public politics in the Severiano de Almeida, Rio Grande do Sul state, Brazil, adapting a methodology viable and based on use of the thematic cartography and Geographic Information Systems GIS, to elaborate a digital database georreferencing, that permit to understand structure and functioning of the natural systems, in the perspective of the use sustainable of the natural resources in the municipal scope. The social-ambient municipal diagnostic procedure, that presents, approximately, 167,45 km2 e 3,868 inhabitants, was developed on the basis of the elaborated topographical map for the Geographic Direction Service (GDS) and digital images of satellite. The results had understood the elaboration of referring maps to the elements structural of the landscape, that by means of a systemic analysis permited understanding of the social-space reality, the elaboration of the ecological-economic zoning it permited to separate the area of the district in five zones that they present degree of distinct fragility. In the prognostic procedure had been analyzed the potentialities, social and economic impediments where they had been defined the lines of direction of general enclosed for all the municipal area, the lines of direction had been elaborated on the basis of criteria and principles established in the disgnostic procedure, with the objective of to preserve the natural characteristics of each area, whereas potentialities are prioritized.